Person-based co-design of a decision aid template for people with a genetic predisposition to cancer - Morton, Kate; Kohut, Kelly; Turner, Lesley; Smith, Sian; Crosbie, Emma J.; Ryan, Neil; Grimmett, Chloe; Eccles, Diana M.; Foster, Claire, The CanGene CanVar Patient Reference Panel, The International Lynch Decision Aid Stakeholder (LDAS) Panel (Frontiers in Digital Health, 2022)
Background People with genetic predispositions to cancer are faced with complex health decisions about managing their risk. Decision aids can support informed, values-based decisions, alongside shared decision-making with a clinician. Whilst diagnoses of genetic predispositions to cancer are increasing, there is no scalable decision aid to support these people. This paper presents an accessible, relevant decision aid template which can be adapted for different predispositions to cancer. Methods The decision aid template was co-developed with 12 patients affected by cancer and informed by empirical and theoretical literature. In addition, consultations were conducted with a further 19 people with Lynch syndrome; a specific genetic predisposition to cancer. Clinical stakeholders were consulted regularly. Coulter's framework for decision aid development guided the process, and these activities were complemented by the International Patient Decision Aid Standards, and the latest evidence on communicating risk in decision aids. Programme theory was developed to hypothesise how the decision aid would support decision-making and contextual factors which could influence the process. Guiding principles co-developed with the patient panel described how the decision aid could effectively engage people. Results The in-depth co-design process led to the identification of five core components of an accessible decision aid template for people with a genetic predisposition to cancer: defining the decision; a table showing implications of each option; optional further details such as icon arrays to show tailored risk and personal narratives; values clarification activity; and a summary to facilitate discussion with a clinician. Specific guidance was produced describing how to develop each component. The guiding principles identified that the decision aid template needed to promote trust, reduce distress, and be comprehensive, personally relevant and accessible in order to engage people. Conclusion Adopting a co-design process helped ensure that the decision aid components were relevant and accessible to the target population. The template could have widespread application through being adapted for different genetic predispositions. The exact content should be co-designed with people from diverse backgrounds with lived experience of the specific predisposition to ensure it is as useful, engaging and relevant as possible.